LEGAL PERSONALITY OF PUBLIC LEGAL FORMATION - Sergeev Dmitry Borisovich (Scientific Journal of Pedagogy and Economics, 2021)
In article public legal formation is studied as the organizational and legal embodiment of state and in the publication analyzes using the normative and systematic methods, as well as analysis and synthesis, the content of the Russian legislation and the works of legal scholars. The author came to a conclusion that «to be a subject of legal relations» means only to have ability to enter them. Therefore nothing and nobody can treat a sort of such phenomena as a legal entity or subject of legal relationship as ability is one of attributes. When public formation is called legal entity, often on a background the fact it is officials and bodies of public government (public administration and local government) ordered in structure and that the most important function of public formation – right ensuring. According to the author legal personality of public formation and legal personality of its bodies also mutually depend on each other. On the one hand, public formation as phenomenon, ideal in terms of philosophy, cannot carry out any actions as legal entity without actions of people – bodies and officials. On the other hand, state and municipal bodies and officials or act as legal entities – representatives of state or municipality (for example, governor in relations with legal entities which exist out of state), or their legal personality is based on they are recognized as a part of public formation, entering relations with its population or with other bodies and officials of this public formation. At the same time legal personality of public formation is not the sum of legal personality of all public bodies neither particular bodies of public formation, nor all of them combined are legal entities of state or municipal property.